2008
DOI: 10.1029/2007gb003154
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal distribution and succession of dominant phytoplankton groups in the global ocean: A satellite view

Abstract: Phytoplankton plays an important role in the global carbon cycle via the fixation of inorganic carbon during photosynthesis. However, the efficiency of this “biological pump of carbon” strongly depends on the nature of the phytoplankton. Monitoring spatial and temporal variations of the distribution of dominant phytoplankton groups at the global scale is thus of critical importance. Recently, an algorithm has been developed to detect the major dominant phytoplankton groups from anomalies of the marine signal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
313
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(359 citation statements)
references
References 59 publications
23
313
0
2
Order By: Relevance
“…Further studies combining in situ measurements of plankton species abundance and particle traps with high-resolution remote sensing images to differentiate phytoplankton groups (e.g. PHYSAT, see Alvain et al (2008)) and the use of altimetry-derived Lagrangian diagnostics of the surface transport (d'Ovidio et al, 2010) could greatly improve our understanding of phytoplankton bloom dynamics and its potential control on the biological carbon pump in areas of important biogeochemical cycling such as the continental margins. …”
Section: Discussionmentioning
confidence: 99%
“…Further studies combining in situ measurements of plankton species abundance and particle traps with high-resolution remote sensing images to differentiate phytoplankton groups (e.g. PHYSAT, see Alvain et al (2008)) and the use of altimetry-derived Lagrangian diagnostics of the surface transport (d'Ovidio et al, 2010) could greatly improve our understanding of phytoplankton bloom dynamics and its potential control on the biological carbon pump in areas of important biogeochemical cycling such as the continental margins. …”
Section: Discussionmentioning
confidence: 99%
“…Satellite derived data, long-term databases and annual research cruises show that the retreat of sea ice initiates a bloom of diatoms in highly stratified waters and shelf areas (Garibotti et al, 2003a, Seasonal changes in open water area, phytoplankton primary productivity and nutrient concentration in the SSIZ from October to March, where the retreat of the sea ice and rapid nutrient drawdown drive the observed succession of Antarctic phytoplankton communities. Timing and magnitude of changes in SSIZ are adapted from Arrigo et al (2008b) and species succession information taken from Kang et al (2001), Garibotti et al (2003a,b) and Wright et al (2010). 2003b; Alvain et al, 2008;Arrigo et al, 2008b). The spring diatom blooms deplete reserves of nutrients such as iron and silicate (e.g.…”
Section: Southern Ocean Primary Productivitymentioning
confidence: 99%
“…Changes in ecosystem composition, that appear to be driven by climate variability, are already underway: examples include desertification around the Mediterranean Sea (Kéfi et al, 2007), shifts in North Atlantic plankton biomass (Beaugrand et al, 2002), regime shifts in the North Pacific and North Sea (Chavez et al, 2003;Reid et al, 2001;Roemmich and McGowan, 1995) and observed shifts in phytoplankton pigment distributions as seen from satellite (Alvain et al, 2008). Large productivity crashes are also associated with ENSO events in the Pacific (e.g.…”
Section: Phyto-and Zooplanktonmentioning
confidence: 99%
“…New developments in the interpretation of SeaWiFS data (e.g. Aiken et al, 2008;Alvain et al, 2005Alvain et al, , 2006Alvain et al, , 2008Raitsos et al, 2008) are making possible the identification of some phytoplankton functional groups on a global scale.…”
Section: Plankton Biodiversity Functional Groups and Ocean Biomesmentioning
confidence: 99%